A feição privatista na gestão do ensino médio público em tempo integral no Amapá (2016-2018) - NUNES, José Almir Viana (UNIFAP – Universidade Federal do Amapá, 2022)
The privatization of education is present in Brazil and manifests itself in several ways, including the participation of business groups in the definition of the national public agenda. In this perspective, the general objective of the research was to analyze the relations of the State Reform with the implementation of educational policies, particularly in the implementation of public high school in Full Time, in the state of Amapá. In relation to specific objectives, they consisted of describing the Full-Time Education policy, marking the factors that determined the state implementation; to identify the mechanisms of action of the Institute of Co-responsibility for Education (ICE) in the process of implementing this policy and to investigate the privatist aspect in the management of State Schools in Full Time in Amapá. As to the research problem, the question was asked: why is full-time high school / EMTI becoming a favorable field for the implementation of the privatist phenomenon of Basic Education in Amapá? Derived from the problem, we have the following guiding questions: how is the privatist phenomenon of Public High School in Brazil and Amapá revealed? What speeches and practices have been constituted in the relationship between the privatist feature and the subjects directly involved in the process of implementing EMTI in Amapá? The time limit for investigation was the year 2016, when the policy was implemented in the State of Amapá, reaching 2018, the implementation phase. Methodologically, it is a field research, in which analysis of national and state documents referring to the Full-Time Education Policy and semi-structured interviews with twelve subjects was carried out (1 consultant from the Ministry of Education / MEC, 2 consultants from ICE , 1 General manager of the EMTI implementation team of the Amapá / SEED Secretariat of Education and 8 managers of the eight local schools). Theoretical references and empirical data are the main sources of the study, which is guided by the materialistic-historical theoretical-methodological perspective. For the analysis of the interviews, the theory of discourse theorized by Mikhail Bakhtin (1997) was considered, which allowed us to infer that there is in the EMTI, the management policy that expresses the culture of goals, spreadsheet of indicators, productivity indexes, evaluation and the ideology of educational quality and that government action to implement ETI in the state of Amapá has reinforced the commodification of the school process, guaranteeing the hegemony of neoliberal policies in the field of education.